Long-Term (10-Year) Gastrointestinal and Genitourinary Toxicity after Treatment with External Beam Radiotherapy, Radical Prostatectomy, or Brachytherapy for Prostate Cancer. (11th April 2012) - Hunter, Grant K.; Reddy, Chandana A.; Klein, Eric A.; Kupelian, Patrick; Angermeier, Kenneth; Ulchaker, James; Chehade, Nabil; Altman, Andrew; Ciezki, Jay P.
Abstract : Objective. To examine gastrointestinal (GI) and genitourinary (GU) toxicity profiles of patients treated in 1999 with external beam radiotherapy (RT), prostate interstitial brachytherapy (PI) or radical prostatectomy (RP). Methods. TThe records of 525 patients treated in 1999 were reviewed to evaluate toxicity. Late GI and GU morbidities were graded according to the RTOG late morbidity criteria. Other factors examined were patient age, BMI, smoking history, and medical co-morbidities. Due to the low event rate for late GU and GI toxicities, a competing risk regression (CRR) analysis was done with death as the competing event. Results. Median follow-up time was 8.5 years. On CRR univariate analysis, only the presence of DM was significantly associated with GU toxicity grade >2 (P = 0.43, HR 2.35, 95 % Cl = 1.03–5.39). On univariate analysis, RT and DM were significantly associated with late GI toxicity. On multivariable analysis, both variables remained significant (RT: P = 0.038, HR = 4.71, CI = 1.09 –20.3; DM: P = 0.008, HR = 3.81, 95 % Cl = 1.42–10.2). Conclusions. Late effects occur with all treatment modalities. The presence of DM at the time of treatment was significantly associated with worse late GI and GU toxicity. RT was significantly associated with worse late GI toxicity compared to PI and RP.